THE ETHNO MATHEMATICS INTEGRATED TEACHING MODULE TO INCREASE THE MATHEMATICAL PROBLEM SOLVING SKILLS - Nurhadi, Muhammad; Yerizon, Yerizon; Arnawa, I Made; Yarman, Yarman; Arnellis, Arnellis (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
A teaching module equipped with LKPD can actualize a more effective and fun learning process, also can increase the mathematical problem solving skills that should mastered by the students. However, from the data acquisition results there are still many students who have difficulties in solving and resolving the mathematical problems given. So, there need innovation in using teaching module equipped with ethno mathematic integrated LKPD which can assist to increase the mathematical problem solving skills of the students. This research aims to comparing the mathematical problem solving ability of VII grade junior high school students taught with ethno mathematic integrated teaching modules with students taught with conventional methods.  This research is a quasy experiment and research design uses is randomized control group only design. The research population are whole grade seventh students of Al Madinah Islamic Boarding School which amounts are 115 people. The instrument uses is mathematical problem solving skills test. Based on the research results, the average score for experimental class students was 78,33 and the average score for control class students was 70,14. After testing the hypothesis with the t test, it is found that the ability to solve mathematical problems skills of those learning through teaching modules equipped with ethno mathematics integrated LKPD with problem based learning model are higher than the mathematical problem solving skills of those learning through conventional learning model.Modul ajar yang dilengkapi dengan LKPD dapat mewujudkan proses pembelajaran yang lebih efektif dan menyenangkan, serta dapat meningkatkan kemampuan pemecahan masalah matematis peserta didik yang harus dikuasai oleh peserta didik. Namun, dari hasil perolehan data yang didapatkan masih banyak peserta didik yang kesulitan dalam memecahkan dan menyelesaikan persoalan matematika yang diberikan. Sehingga, perlu adanya inovasi dalam penggunaan modul ajar disertai LKPD terintegrasi etnomatematika yang dapat membantu meningkatkan kemampuan pemecahan masalah peserta didik. Penelitian ini bertujuan untuk membandingkan kemampuan pemecahan masalah matematis peserta didik kelas VII SMP/MTs yang diajar dengan modul ajar terintegrasi etnomatematika dengan peserta didik yang diajar dengan metode konvensional. Penelitian ini merupakan penelitian quasy experiment dan rancangan penelitian yang digunakan adalah randomized control group only design. Populasi penelitian ini adalah seluruh peserta didik kelas VII SMP Al Madinah Islamic Boarding School yang berjumlah 115 orang. Instrumen yang digunakan berupa tes kemampuan pemecahan masalah matematis. Berdasarkan hasil penelitian diperoleh nilai rata-rata peserta didik kelas eksperimen  dan nilai rata-rata peserta didik kelas kontrol . Setelah dilakukan uji hipotesis dengan uji t diperoleh bahwa kemampuan pemecahan masalah matematis yang belajar menggunakan modul ajar dilengkapi LKPD terintegrasi etnomatematika dengan model pembelajaran problem based learning lebih tinggi dari pada kemampuan pemecahan masalah matematis yang belajar menggunakan modul ajar dengan model pembelajaran konvensional.